2011
DOI: 10.1186/1743-422x-8-73
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic genetic characterization of the ORF7 gene of porcine reproductive and respiratory syndrome virus (PRRSV) in China

Abstract: BackgroundPorcine reproductive and respiratory syndrome virus (PRRSV) exhibits extensive genetic variation. The outbreak of a highly pathogenic PRRS in 2006 led us to investigate the extent of PRRSV genetic diversity in China. To this end, we analyzed the Nsp2 and ORF7 gene sequences of 98 Chinese PRRSV isolates.ResultsPreliminary analysis indicated that highly pathogenic PRRSV strains with a 30-amino acid deletion in the Nsp2 protein are the dominant viruses circulating in China. Further analysis based on ORF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In 2006, an atypical PRRS outbreak in China was caused by an emerging highly-pathogenic PRRSV (HP-PRRSV) strain with a discontinuous deletion of 30-amino acid in the Nsp2 coding region in comparison with classical PRRSV strains [9,10]. Since then, the HP-PRRSV strain, which caused a more severe pneumonia and higher mortality than the classical PRRSV, has become the dominant strain found in China [11,12]. The immense genetic variability in the coding region of Nsp2 suggests that Nsp2 may play a limited role in viral replication but likely to play a very important part in modulating virus pathogenesis and the inflammation response in pigs during infection [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, an atypical PRRS outbreak in China was caused by an emerging highly-pathogenic PRRSV (HP-PRRSV) strain with a discontinuous deletion of 30-amino acid in the Nsp2 coding region in comparison with classical PRRSV strains [9,10]. Since then, the HP-PRRSV strain, which caused a more severe pneumonia and higher mortality than the classical PRRSV, has become the dominant strain found in China [11,12]. The immense genetic variability in the coding region of Nsp2 suggests that Nsp2 may play a limited role in viral replication but likely to play a very important part in modulating virus pathogenesis and the inflammation response in pigs during infection [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…1, analysis of the complete deduced amino acid sequence of N-protein from the 36 PRRSV isolates shared common six mutations with Chinese HP-PRRSV strains. These mutations were also detected in other HP-PRRSV strains isolated in China [11,12] . Compared to classical strain CH-1a, four mutations at position 46, 91, 109 and 117 were just observed in HP strains.…”
Section: Discussionmentioning
confidence: 60%
“…N protein contains conserved nucleotide determinants such as nuclear localization signal (NLS), nuclear export signal (NES). Previous study had demonstrated that mutations at 43 and 44 within the NLS weaken viral replication [24] , NLS motif such as "Pat7" located at position 41-47 (PGKKNKK) might block the recognition of the epitopes [11] . In our study, the substitution K46R observed in 36 isolates and also in Chinese HP-PRRSV strains might influence to its function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations